P087: Cellulitis and erysipelas management at an academic emergency department: current practice vs the literature. (15th May 2017) - Martin, J.; Wilson, C.R.; Chaplin, T.
Abstract : Introduction: Cellulitis and erysipelas are common presentations for the general practitioner. Antibiotic therapy targeting beta-hemolytic streptococci and Staphylococcus aureus is the mainstay of treatment for children and adults with these infections. Although evidence-based Canadian guidelines for appropriate management exist, inconsistent practices persist. Our objective was to determine the level of adherence to current evidence by emergency physicians at two academic hospitals in Kingston, Ontario.Methods: We conducted a retrospective chart review of 200 randomly selected electronic medical records. Records belonged to patients with a discharge diagnosis of cellulitis or erysipelas who were seen in the emergency departments of Kingston General Hospital or Hotel Dieu Hospital between January 1 and June 30, 2015. We manually collected data describing patient demographics, medical history, and medical management.Results: There were 707 total visits to the emergency departments in the study period for cellulitis or erysipelas. In our random sample, for those diagnosed with cellulitis, 44% received oral cephalexin alone, which was the most common form of therapy for uncomplicated infection. Of all the patients who received any antibiotics, 36% received at least one dose of parenteral antibiotics, despite only 6.7% showing systemic signs of illness. Emergency physicians chose ceftriaxone for 88% of the patients who received parenteral antibiotics.Conclusion: There was wide variation in antibiotic selection and route of administration for patients with cellulitis or erysipelas. Ceftriaxone was chosen for most patients receiving parenteral antibiotics, but it may not have been the most effective antibiotic in some cases. Overuse of antibiotics is common, and we believe medication choice should be justified based on disease severity, spectrum of activity, and regional antibiotic resistance patterns, among other factors. In conclusion, we found that emergency physicians could more closely align management plans with current guidelines to improve management of uncomplicated infection and reduce unnecessary administration of parenteral antibiotics.